Identification of the Zingiberaceae Family in Banuayu Village, South Kikim District, Lahat Regency, South Sumatra - Sasmaini, Deka; Lestari, Weni; Hapida, Yustina; 'Aini, Kurratul; Nurokhman, Amin (Jurnal Biologi Tropis, 2024)
Zingiberaceae family plants are spice plants that are widely preserved in Banuayu village, South Kikim sub-district, Lahat district. Zingiberaceae plants are also used by the community as cooking spices, traditional medicines, food and drink ingredients and food coloring. This research aims to determine the species of the Zingiberaceae family in Banuayu village. This type of research on the identification of the Zingiberaceae family uses the exploration method. The results of the research show that there are 10 species of the Zingiberaceae family consisting of bangle (Zingiber montanum (J. Konig) Link ex A. Dietr), galangal (Kaempferia galanga L.), white turmeric (Curcuma zedoaria (Christm.) Roscoe), yellow turmeric (Cucurma longa L.), red galangal (Alpinia purpurata (Vieill.) K.Schum), white galangal (Alpinia galanga (L.) Willd.), white ginger (Curcuma zedoaria (Christm.) Roscoe), red ginger (Zingiber officinale Roscoe), combrang (Etlingera elatior (Jack) R.M.Sm.), and ginger (Curcuma zanthorrhiza Roxb.).